2019
DOI: 10.1029/2018jg004808
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tree Species on Soil Organic Carbon Content in South Korea

Abstract: The effects of tree species on soil organic carbon (SOC) content have been evaluated in many studies, but only with a relatively small number of sample plots, resulting in ambiguous conclusions. Here we used a total of 595 forest plots in South Korea to investigate the role of four grouped tree species—pines, oaks, other conifers, and other deciduous trees—in the forest SOC content in both forest floors and mineral soils. Significant differences were observed in SOC content among the groups. Pines contained 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 42 publications
4
9
0
2
Order By: Relevance
“…First, the lack of significant differences in C:N ratios between the PRF sites (Table 3) indicates that the rate of SOC stock accumulation or release through organic matter decomposition and mineralization in both sites could be the similar. This is in line with studies in South Korea that illustrate that the rate of SOC storage in a study site is influenced by the soil C:N ratio (Cha et al 2019;Kim et al 2016). Second, the cultivation style of the paddy rice farm prior to reforestation or disturbances in the DNF might not have been enough to destabilize SOC and STN stocks.…”
Section: Discussionsupporting
confidence: 90%
“…First, the lack of significant differences in C:N ratios between the PRF sites (Table 3) indicates that the rate of SOC stock accumulation or release through organic matter decomposition and mineralization in both sites could be the similar. This is in line with studies in South Korea that illustrate that the rate of SOC storage in a study site is influenced by the soil C:N ratio (Cha et al 2019;Kim et al 2016). Second, the cultivation style of the paddy rice farm prior to reforestation or disturbances in the DNF might not have been enough to destabilize SOC and STN stocks.…”
Section: Discussionsupporting
confidence: 90%
“…Our results also indicated that above-ground species of tree is important for above-ground and soil organic C stocks, explaining 30% and 10% of variation, respectively. This is consistent with previous findings for aboveground biomass in a Pinus kesiya forest and soil organic C in pine, oak, conifer, and deciduous forests (Cha et al, 2019;Li et al, 2018). The importance of plant species for soil properties has been shown in several studies.…”
Section: Soil Characteristics and Ecosystem Propertiessupporting
confidence: 92%
“…Furthermore, large inter-site variations of soil properties (Boca et al, 2014;Wang et al, 2016) possibly obscure inter-species effects (Wang, Wang, & Chang, 2017). It is possible to compare broadleaf and conifer species by designing experiments within a single site (Cha, Cha, & Oh, 2019;Kooch, Rostayee, & Hosseini, 2016;Sariyildiz et al, 2015;Tang & Li, 2013), but when multiple-species were across large-scale sites, the site variations need to be statistically excluded.…”
Section: Introductionmentioning
confidence: 99%